Impact factor pressures, scientific practices, and the place of survey articles in the history of economics - Erich Pinzón-Fuchs; Cléo Chassonnery-Zaïgouche; Catherine Herfeld (Duke University, Center for the History of Political Economy (CHOPE), 2019)
The literature in the history of economics has grown to an extent that it is almost impossible for an individual to read, study, and assimilate all the recent works even in a specialized area. Other disciplines have coped with similar growth by developing mechanisms that help members keep up-to-date with the latest scholarly contributions and methodological trends - mechanisms including survey articles. But in the history of economics, and in the larger academic context, survey articles bring serious challenges. One challenge is their unintended consequences for rankings of history of economics journals on the basis of citation measures, as evidenced by Clarivate Analytics decision to exclude three major history of economics journals from its 2018 Journal Citation Report. In this paper, we take this case as representative for illustrating the functions, advantages, and challenges of survey articles. We argue that survey articles should play an important role in the history of economics as mechanisms that mitigate narrow specialization, provide greater visibility, support reflexivity, set and evaluate the research agenda of the field, and work as a 'technology of distance' builds up trust among historians of economics.
Keywords: 330; Survey Article; Review Article; Clarivate Analytics; Impact Factors; Publishing and Scientific Practices; History of Economics